Comparative Study Of Changes in SNI 1727 (2013 – 2020) and SNI 1726 (2012 – 2019) - Andina Prima Putri; Christiano Credidi Septino Khala; Gangsar Rizqon Prayogi (Universitas Islam Sultan Agung, 2022)
Being one of the largest developing countries, Indonesia has high intensity of infrastructure development. Because of its exact location between the Pacific plate and Eurasian plate, it is necessary to consider the earthquake load in planning a building or other structure. The fundamental period is a function of the lateral stiffness of a building, which will play an important role in carrying lateral loads, such as earthquakes. Earthquake loads experienced by the structure will result in deformation of the building. For building planning in Indonesia, national standards (SNI,) which are continuously adapted to the conditions of the earth and technological developments in construction, are used. This study aims to determine the impact of changes to the standards applied in terms of changes in cross-sectional dimensions, fundamental periods, and building deformation, using modeling in the auxiliary program. Compared with modeling the existing structure in the initial state (model 1), the existing structure with the latest loading (model 2), and the planning results using the latest standard (model 3).Based on the results of the analysis, it was found that the beam dimension changes in the form of an 88% increase in cross-sectional area on the 2nd and 3rd floors of the B9 beam, the largest change in the column cross-sectional dimensions on the K3 column on the 4-7th floor and the K8 column on the 3-7th floor with a large increase of 104%, the change in the fundamental period model 3 increased by 22% from model 1 and increased by 19% from the period model 2, and obtained a change in the form of displacement. X direction in model 3 experienced a maximum increase of 210% against model 1 on the roof floor and in model 3 against model 3 2 increased by 37% on the roof floor for displacement Y direction in model 3 experienced a maximum increase of 192% against model 1 on the roof floor and an increase of 29% against model 2 on the roof.